Three-dimensional assessment of two different canine retraction techniques: a randomized split-mouth clinical trial - Şuayip Akın; Hasan Camcı (SpringerOpen, 2021)
Abstract Introduction The aim of this split-mouth trial was to compare power-arm sliding (PAS) and direct sliding (DS) canine retraction mechanics in terms of speed, rotation, angulation, and anchorage loss. Methods Thirty-six class II division 1 patients (20 females, 16 males; mean age, 16.94 ± 3.23) requiring upper first premolar extraction were included in the study. Miniscrews were used as anchorage units, and a retraction force of 150 gr was applied from the power arm on one side and from the bracket on the opposite side by using elastomeric chains. Randomization was achieved by block randomization with a 1:1 allocation ratio either to the right or the left with allocations concealed in opaque, sealed envelopes. Digital models were acquired using an intraoral scanner at the beginning of the retraction (T0), the first month (T1), the second month (T2), and the third month (T3). Before the scans, the archwire was removed, and custom metal jigs were inserted into the vertical slot of the canine brackets to evaluate the canine angulation. The digital models of each patient were separately superimposed with the local best-fit algorithm, and the retraction rate, angulation, rotation, and anchorage loss were measured. The digital measurements were performed using the Geomagic Control X software. Results The DS technique's total retraction rate was higher than that of the PAS technique (2.09 and 1.57, respectively, p = .002). There was, however, no significant difference between the two techniques in terms of angulation, rotation, and anchorage loss. A negative correlation was observed between the retraction rate and age, but it was not statistically significant. No significant difference was observed between the retraction rates of female and male participants in either retraction technique. Conclusions For both orthodontists and patients, the DS technique is simpler and more convenient; thus, it is the preferred method for canine retraction. Trial registration The trial was not registered. Protocol The protocol was not published before the trial commencement.